The SGK3-triggered ubiquitin–proteasome degradation of podocalyxin (PC) and ezrin in podocytes was associated with the stability of the PC/ezrin complex. Issue 11 (November 2018) - Yuan, Ya-Pei; Zhao, Hong; Peng, Li-Qin; Li, Zi-Fang; Liu, Song; Yuan, Cheng-Yan; Mwamunyi, Mercy-Julian; Pearce, David; Yao, Li-Jun
Abstract Podocyte damage is commonly accompanied by destabilization of the podocalyxin (PC)/ezrin complex. Serum- and glucocorticoid-inducible kinase 3 (SGK3) plays a role in the maintenance of podocyte function, but the details of this role are poorly understood. Herein we demonstrated that SGK3 and its downstream target protein neural precursor cell expressed developmentally downregulated protein 4 subtype 2 (Nedd4-2) triggered PC and ezrin interaction. In adriamycin (ADR)-induced nephritic mice, and after puromycin aminonucleoside (PAN)-induced podocyte damage in vitro, PC and ezrin protein expression levels decreased significantly, while Nedd4-2 activity increased. Moreover, PAN treatment increased PC and ezrin ubiquitination and decreased PC/ezrin interaction in cultured mouse podocytes. The downregulation of SGK3 activity in mouse podocytes resulted in decreased PC and ezrin protein expression and increased the ubiquitin–proteasome degradation of PC and ezrin. Furthermore, upregulation of SGK3 activity mostly reversed the PAN-induced decrease in PC and ezrin protein expression. Overexpression of Nedd4-2 led to decreased ezrin protein expression via the upregulation of ezrin ubiquitination. In contrast, Nedd4-2 knockdown resulted in increased ezrin protein expression but decreased ezrin ubiquitination. In PC-transfected human embryonic kidney (HEK293T) cells, SGK3 activity downregulation and Nedd4-2 overexpression resulted in decreased PC/ezrin interaction. These results suggested that SGK3 triggers the ubiquitin–proteasome degradation of PC and ezrin, while the SGK3/Nedd4-2 signaling pathway regulates ezrin, but not PC, ubiquitination. Thus SGK3 helps to regulate podocyte function by maintaining the stability of the PC/ezrin complex.